2019
DOI: 10.1371/journal.pone.0217562
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal status is associated with a high risk for residual disease after cervical conization with positive margins

Abstract: Background We aimed to determine demographic and clinicopathological predictors for residual disease in women with cervical intraepithelial neoplasia (CIN 2/3) with endocervical cone margin involvement. Methods and findings A cross-sectional study was conducted. The eligible patients were women who underwent hysterectomy as a treatment option after having a positive endocervical margin for CIN 2/3 in cervix conization specimens from 2000 to 2015. The patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
6
12
1
Order By: Relevance
“…Previous studies have reported that menopausal status and age are both associated with residual lesions after conization. 15 , 17 In the present study, in 56 (43.41%) post-menopausal women, residual disease was discovered in hysterectomy specimens, representing a rate higher than previously reported data in younger patients. This may be explained by the specific study population of post-menopausal women and the identification of residual lesions in the hysterectomy specimens.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have reported that menopausal status and age are both associated with residual lesions after conization. 15 , 17 In the present study, in 56 (43.41%) post-menopausal women, residual disease was discovered in hysterectomy specimens, representing a rate higher than previously reported data in younger patients. This may be explained by the specific study population of post-menopausal women and the identification of residual lesions in the hysterectomy specimens.…”
Section: Discussioncontrasting
confidence: 57%
“…Several previous studies have evaluated clinical and pathological predictors of the persistence of or residual CIN and cervical cancer. 3,[5][6][7][8][9][10][13][14][15][16][17] However, only a few studies have examined whole uterine specimens after hysterectomy 13 and have focused on post-menopausal patients alone. These studies differ from each other methodologically, including the study populations and analysis of variables.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous studies have suggested that the possible risk factors for residual lesions after cervical conization mainly include positive margins of the specimen, involvement of the lateral margin of the cervical canal, involvement of the lateral margin of the cervical canal and outer orifice, positive specimen from ECC, menopause, persistent infection of high-risk HPV after cervical conization, and decreased or suppressed immune function [ 13 , 14 ]. Many factors affect the condition of the margin after CKC, including age, menopausal status, glandular involvement, smoking, infection, training level of the operator, and other factors [ 15 , 16 ]. In this study, the clinicopathological characteristics of 1309 women of child-bearing age after initial CKC and 245 cases of women with positive margins who accepted subsequent surgery within three months were retrospectively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Many factors affect the condition of the margin after CKC, including age, menopausal status, glandular involvement, smoking, infection, training level of the operator, and other factors. [15,16] In this study, we retrospectively analyzed the clinicopathological characteristics of 1,309 women of child-bearing age after initial CKC and 245 cases of women with positive margins who accepted subsequent surgery within three months. We found that a major cytology abnormality (including HSILs and ASC-Hs), high-risk HPV infection type III transformation zone, positive ECC result, and multiple quadrant involvement were the common risk factors for positive margins and residual lesions.…”
Section: Univariate and Multivariate Analyses Of Risk Factors For Resmentioning
confidence: 99%